(untitled) (Revista de Ciências Agroveterinárias, 2018)
Agroforestry systems have been considered options for sustainable intensification of agricultural production, especially in regions with tropical climate and sandy soils. The objective of this study was to evaluate the performance of soybean crops in agroforestry systems with Eucalyptus urograndis in the Northwest region of the state of Paraná, Brazil. The systems were implanted in October 2009, using single and double rows of eucalyptus. Soybean crop performance was evaluated in the growing season between 2015/16 in four experiments. In each experiment, a spatial conformation of eucalyptus plants was used: simple row with low density of trees, simple row with high density, double rows with low density and double rows with high density. A contiguous area without tree interference was used as control group. In the four experiments, soybean growth and nitrogen content in dry mass at full bloom were not significantly reduced, due to the presence of eucalyptus. The reduction of soybean yield caused by tree interference ranged from 40% to 43% compared to the control group. Protein and oil contents in soybean grains were not altered by tree interference.